2019
DOI: 10.4103/sjg.sjg_447_18
|View full text |Cite
|
Sign up to set email alerts
|

Greater prevalence of comorbidities with increasing age: Cross-sectional analysis of chronic hepatitis B patients in Saudi Arabia

Abstract: Background/Aims: Middle Eastern countries, including Saudi Arabia to some extent, are endemic for chronic hepatitis B (CHB) infection which could be associated with high mortality and comorbidities risk. However, limited data characterizing this CHB population exists. Our aim was to characterize and compare CHB patients in 2015 with those in 2010 and 2012 in Saudi Arabia. Patients and Methods: We conducted and compared three cross-sectional analyses of adult patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 30 publications
5
22
0
Order By: Relevance
“…10%). [38] This suggests that although the overall prevalence of HBV has decreased dramatically, the associated burden of end-stage liver disease secondary to CHB is likely to increase drastically in KSA in the next 20 years due to aging of the previously infected children. [39]…”
Section: Epidemiologymentioning
confidence: 99%
“…10%). [38] This suggests that although the overall prevalence of HBV has decreased dramatically, the associated burden of end-stage liver disease secondary to CHB is likely to increase drastically in KSA in the next 20 years due to aging of the previously infected children. [39]…”
Section: Epidemiologymentioning
confidence: 99%
“…A study in Vietnam [30] reported a prevalence rate of 9.0% of HBV, which was close to the rate among hill tribe adults in Thailand. The prevalence has increased according to age which is consisted with a study in China, [31,32]. It is highly recommended that the HBV vaccine be implemented in high-prevalence areas by the United States Advisory Committee on immunization practice [27].…”
Section: Discussionmentioning
confidence: 99%
“…A study in Vietnam [ 30 ] reported a prevalence rate of 9.0% of HBV, which was close to the rate among hill tribe adults in Thailand. The prevalence has increased according to age which is consisted with a study in China, [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…I read with great interest the article by Sanai et al . [1] recently published in this Journal. The authors utilized data from the Systematic Observatory Liver Disease Registry (SOLID), from the Liver Disease Research Center based in Saudi Arabia.…”
mentioning
confidence: 99%
“…In this observational retrospective study authors reported that chronic hepatitis B (CHB) patients in Saudi Arabia were older in 2015 compared to 2010 and 2012. [1] The study showed that older patients had a higher chance to develop comorbidities, including cirrhosis, hepatocellular carcinoma (HCC), coronary artery disease (CAD), and exhibited a greater likelihood to have been treatment experienced or undergone treatment switch.…”
mentioning
confidence: 99%